2021
DOI: 10.3389/fsufs.2021.605610
|View full text |Cite
|
Sign up to set email alerts
|

Organic Fertilizer Based on Rhizophagus intraradices: Valorization in a Farming Environment for Maize in the South, Center and North of Benin

Abstract: Maize plays an important role in agricultural production systems in all agro-ecological zones of Benin. Despite its importance, its production faces many constraints including soil fertility. One of the ecological technologies aimed at improving agricultural production is the use of soil microorganisms including arbuscular mycorrhizal fungi (AMF). This study aims to evaluate the effectiveness of Rhizophagus intraradices, an indigenous strain, on maize productivity in farmers' areas in the Research and Developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 38 publications
9
5
0
Order By: Relevance
“…This shows that the soils in our study were acidic. This result confirms those of Aguégué et al [32], who showed that the soils of northern Benin were moderately acidic and poor in organic matter. This water pH promotes the growth of fungi, which thrive best in acidic environments [23].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This shows that the soils in our study were acidic. This result confirms those of Aguégué et al [32], who showed that the soils of northern Benin were moderately acidic and poor in organic matter. This water pH promotes the growth of fungi, which thrive best in acidic environments [23].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, soil organic matter, assimilable phosphorus and exchangeable base contents were good for the experiment on the effects of NPK mineral fertilizers and agreed with those obtained by Aguégué et al [32] in northern Benin. Furthermore, these soils had a low level of fertility characterized by high C/N ratios.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the last decade, great efforts have been made to substitute chemical fertilizers with environmentally friendly biostimulants (Kamilova et al, 2015;Liu et al, 2018;Thomas and Singh, 2019;Amogou et al, 2021). The response to microbial biostimulants inoculation on different crops has been widely evaluated, thus showing significant increase in the growth and yields of agricultural crops (Babalola et al, 2020;Agueǵuéet al, 2021b;Adoko et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, great efforts have been made to substitute chemical fertilizers with environmentally friendly biostimulants ( Kamilova et al., 2015 ; Liu et al., 2018 ; Thomas and Singh, 2019 ; Amogou et al., 2021 ). The response to microbial biostimulants inoculation on different crops has been widely evaluated, thus showing significant increase in the growth and yields of agricultural crops ( Babalola et al., 2020 ; Aguégué et al., 2021b ; Adoko et al., 2021a ).…”
Section: Introductionmentioning
confidence: 99%